Industrial Training, Theoretical Achievement, and Practical Achievement in Productive Subjects on the Work Readiness of Culinary Expertise Students - Ni Wayan Suartiningsih; Ni Luh Gede Erni Sulindawati; Ni Wayan Sukerti (Universitas Pendidikan Ganesha, 2026)
Students’ work readiness in vocational education still shows varying levels of achievement that are not fully aligned with industry demands. This condition indicates that the influence of industrial training, theoretical achievement, and practical achievement in productive subjects on students’ work readiness has not yet been comprehensively examined. This study aims to analyze, evaluate, and examine the contribution of industrial training, theoretical achievement, and practical achievement in productive subjects to the development of work readiness among students in the culinary skills competency program. The research employed a quantitative approach with a correlational design. The research subjects consisted of 115 twelfth-grade students in the culinary skills competency program who had completed industrial training. Data were collected through questionnaires to measure industrial training and work readiness, as well as report card documentation to assess theoretical and practical achievement in productive subjects. The research instruments were tested for validity and reliability prior to data collection. Data analysis was conducted using descriptive analysis, simple linear regression, and multiple linear regression. The findings revealed that industrial training, theoretical achievement, and practical achievement partially and simultaneously have a positive and significant effect on work readiness, with industrial training emerging as the most dominant variable. In general, it can be concluded that students’ work readiness is the result of the integration of knowledge mastery, practical skills, and authentic work experience. The implications of this study highlight the importance of strengthening collaboration with industry and continuously integrating theoretical and practical learning to enhance students’ work readiness.